Invertebrate zoology - Engemann, Joseph G.; Hegner, Robert William (New York : Macmillan Publishing Company, 1981)
This approach also provides a more flexible text with greater usefulness in both lectures and laboratory.
1. Basic principles of invertebrate zoology -- 2. Protozoa -- 3. Phylum porifera -- 4. Phylum coelenterata -- 5. Phylum Platyhelminthes -- 6. Phylum aschelminthes -- 7. Minor phyla -- 8. Phylum annelida -- 9. Phylum mollusca -- 10. Phylum arthropoda.
Includes bibliographical references and index.
Keywords: INVERTEBRATES -- ZOOLOGY